Adipocytes‐Derived Exosomal microRNA‐1224 Inhibits M2 Macrophage Polarization in Obesity‐Induced Adipose Tissue Inflammation via MSI2‐Mediated Wnt/β‐Catenin Axis. Issue 18 (28th July 2022) - Zhang, Dongdong; Yao, Xiaoyan; Teng, Yaqin; Zhao, Tiantian; Lin, Liangyan; Li, Yuanyuan; Shang, Hongxia; Jin, Yongjun; Jin, Qingsong
Abstract : Scope: Phenotypic switch of macrophage polarization in adipose tissue has been associated with obesity‐induced adipose tissue inflammation (OATI). Therefore, this study aims to explore the possible mechanism of adipocytes‐derived exosomes (ADEs) carrying microRNA‐1224 (miR‐1224) in M2 macrophage polarization of OATI. Methods and results: miR‐1224‐knockout (miR‐1224‐KO) mice for this study, and isolated primary adipocytes from high‐fat diet (HFD) or normal diet (SD)‐fed mice are developed. ADEs are extracted and cocultured with bone marrow‐derived macrophages (BMDMs). The macrophagic crown‐like structures (CLS) and M1 and M2 phenotype macrophages in epididymal white adipose tissue (epiWAT) are observed by immunohistochemistry and flow cytometry. The obtained data indicate that miR‐1224 is highly expressed in adipose tissues and adipocytes of obese mice. miR‐1224 knockout decreases CLS number and increases M2 macrophages polarization in epiWAT. In addition, miR‐1224 can be transferred to BMDMs via ADEs, which targeted musashi RNA binding protein 2 (MSI2) expression and inactivated Wnt/β‐catenin pathway, inhibiting macrophage M2 polarization and promoting inflammatory factor release. Conclusion: Exosomal miR‐1224 derived by adipocytes targets MSI2 and blocks the Wnt/β‐catenin pathway, which inhibits macrophage M2 polarization and promotes inflammatory factor release, ultimately promoting OATI. Abstract : A molecular mechanism diagram illustrating the role of ADEs‐shuttled miR‐1224 on OATI via MSI2‐dependent Wnt/β‐catenin pathway. ADEs‐shuttled miR‐1224 down‐regulates the expression of MSI2 to inactivate the Wnt/β‐catenin signaling, which suppresses macrophage M2 polarization and promotes inflammatory factor release, consequently promoting the occurrence and development of OATI.